ISOLASI DAN ELUSIDASI SENYAWA ALKALOID DALAM BIJI MAHONI (Swietenia mahagoni Jacq) - Mamay Maslahat; Helen Lusiana; Obie Farobie (Universitas Nusa Bangsa, 2012)
Isolation and Structure Elucidation of Alkaloid Compounds of Mahoni Seed (Swietenia mahagoni Jacq) Â Â Â Â Â Â Â Â Â Along with rising of the term â€˜back to natureâ€, many people have been using traditionally medicinal plants to overcome variety of diseases. Swietenia mahagoni Jacq seeds have potency to treat various diseases including high blood diseases, diabetes, rheumatism, fever, colds, and eczema. This study aimed to isolate and identify the alkaloid compounds found in mahogany seeds (Swietenia mahagoni Jacq). This research was conducted in 3 stages, namely the sample extraction by using methanol and acetic acid, determining the best eluent by using thin-layer chromatography and column chromatography and characterization of compounds by using UV, FTIR, 1H NMR and 13C NMR spectrophotometer. The best eluent from this research was chloroform : methanol with ratio of 90:10 and 95:5. Result of phytochemical test with Mayer and Dragendorf reagent showed that crude extract of mahoni contain alkaloid compound. Results of structure elucidation with UV, FTIR, 1H NMR, and 13C was assumed that alkaloid compound contained in mahoni was 3,6,7-trimethoxy-4-methyl-1,2,3,4-tetrahydroisoquinoline.Keywords : alkaloid compounds, Swietenia mahagoni Jacq, structure elucidation, chromatoghraphyÂ ABSTRAKÂ Â Â Â Â Â Â Â Â Seiring dengan meningkatnya semangat â€œback to nature